Free‐Standing Polyurethane Nanofiber/Nets Air Filters for Effective PM Capture. Issue 46 (17th October 2017) - Zuo, Fenglei; Zhang, Shichao; Liu, Hui; Fong, Hao; Yin, Xia; Yu, Jianyong; Ding, Bin
Abstract: The filtration performance and light transmittance of nanofiber air filters are restricted by their thick fiber diameter, large pore size, and substrate dependence, which can be solved by constructing substrate‐free fibrous membranes with true nanoscale diameters and ultrathin thicknesses, however, it has proven to be extremely challenging. Herein, a roust approach is presented to create free‐standing polyurethane (PU) nanofiber/nets air filters composed of bonded nanofibers and 2D nanonets for particular matter (PM) capture via combining electrospinning/netting technique and facile peel off process from designed substrates. This strategy causes widely distributed Steiner‐tree structured nanonets with diameters of ≈20 nm and bonded scaffold nanofibers to assemble into ultrathin membranes with small pore size, high porosity, and robust mechanical strength on a large scale based on ionic liquid inspiration and surface structure optimization of receiver substrates. As a consequence, the resulting free‐standing PU nanofiber/nets filters exhibit high PM1–0.5 removal efficiency of >99.00% and PM2.5–1 removal efficiency of >99.73%, maintaining high light transmittance of ≈70% and low pressure drop of 28 Pa; even achieve >99.97% removal efficiency with ≈40% transmittance for PM0.3 filtration, and robust purification capacity for real smoke PM2.5, making them promising high‐efficiency and transparent filtration materials for various filtration and separation applications. Abstract : A free‐standing nanofiber/nets air filter assembled by 2D nanonets (≈20 nm) and bonded nanofibers is created by combining an electrospinning/netting technique and peel off process from designed substrates. In virtue of small pore size, high porosity, and free‐standing capacity, the ultrathin filter can achieve removal efficiency of >99.00%, light transmittance of ≈70% for PM1–0.5 filtration, and even >99.970% removal for PM0.3 filtration.